Use of the functional luminal imaging probe in pediatrics: A comparison study of patients with achalasia before and after endoscopic dilation and non‐achalasia controls. Issue 12 (19th April 2021) - Benitez, Alain J.; Budhu, Stephen; Burger, Cassandra; Turco, Rossella; Ballester, Lance; Shah, Amit; Lynch, Kristle; Fiorino, Kristin; Menard‐Katcher, Calies; Muir, Amanda B.; Mamula, Petar
Abstract: Background: Achalasia is an esophageal motility disorder characterized by esophagogastric junction (EGJ) dysfunction and impaired esophageal peristalsis with significant impact on quality of life. While the functional luminal imaging probe (FLIP) has been used to assess EGJ distensibility in achalasia, its clinical utility in pediatrics is limited due to absence of normative values and correlations with clinical outcomes in children. Thus, we sought to evaluate FLIP's use in a pediatric achalasia cohort undergoing dilations and non‐achalasia controls. Methods: We conducted a retrospective study of pediatric patients with achalasia who underwent FLIP before and immediately after balloon dilations and compared to a non‐achalasia cohort. Key Results: Thirty patients with achalasia (mean age, 15.2 years; 40% female), including fourteen treatment‐naïve and thirteen controls (mean age, 7.9 years; 61% female) were identified. Median EGJ distensibility index (EGJ‐DI) 2.07 mm 2 mmHg −1 and diameter (9.23 mm) in treatment‐naïve patients were significantly lower compared to controls (EGJ‐DI 6.8 mm 2 mmHg −1 ; diameter 18.61 mm; ( p < 0.001). Balloon dilations resulted in a significant increase in EGJ‐DI immediately after the dilation, particularly in treatment‐naïve patients ( p < 0.001), and a significant improvement in Eckardt scores ( p < 0.001). Conclusions & Inferences: Functional luminal imaging probe measurements of EGJ‐DI in pediatric patients with achalasia are mostly consistent with adult findings. However, normal EGJ‐DI is seen in symptomatic patients, including treatment‐naive, highlighting the need for pediatric reference data. Balloon dilations achieve a significant increase in EGJ‐DI with improvement in Eckardt scores, confirming the therapeutic value of dilations in achalasia management. Abstract : In a pediatric achalasia cohort, a reduction in esophagogastric junction distensibility, and a significant improvement after dilation are seen using the functional luminal imaging probe.